AACR Project GENIE: Powering Precision Medicine through an International Consortium - Fabrice André; Mónica Arnedos; Alexander S. Baras; José Baselga; Philippe L. Bédard; Michael F. Berger; Mariska Bierkens; Fabien Calvo; Ethan Cerami; Debyani Chakravarty; Kristen K. Dang; Nancy E. Davidson; et al. (2017)
The AACR Project GENIE is an international data-sharing consortium focused on generating an evidence base for precision cancer medicine by integrating clinical-grade cancer genomic data with clinical outcome data for tens of thousands of cancer patients treated at multiple institutions worldwide. In conjunction with the first public data release from approximately 19,000 samples, we describe the goals, structure, and data standards of the consortium and report conclusions from high-level analysis of the initial phase of genomic data. We also provide examples of the clinical utility of GENIE data, such as an estimate of clinical actionability across multiple cancer types (>30%) and prediction of accrual rates to the NCI-MATCH trial that accurately reflect recently reported actual match rates. The GENIE database is expected to grow to >100,000 samples within 5 years and should serve as a powerful tool for precision cancer medicine.